Rebuilding urban neighborhoods achievements, opportunities, and limits - Keating, W. Dennis (William Dennis); Krumholz, Norman; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
Reporting the progress in the fight against the ingrained poverty and social problems of many areas within the US, this text includes case studies from many cities which highlight the achievements in such communities.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Urban renewal -- United States; Electronic books